Endocytosis-mediated siderophore uptake as a strategy for Fe acquisition in diatoms - Kazamia, Elena; Sutak, Robert; Paz-Yepes, Javier; Dorrell, Richard G; Vieira, Fabio Rocha Jimenez; Mach, Jan; Morrissey, Joe; Leon, Sébastien; Lam, France; Pelletier, Eric; Camadro, Jean-Michel; Bowler, Chris; et al. (Science advances, 2018)
Phytoplankton growth is limited in vast oceanic regions by the low bioavailability of iron. Iron fertilization often results in diatom blooms, yet the physiological underpinnings for how diatoms survive in chronically iron-limited waters and outcompete other phytoplankton when iron becomes available are unresolved. We show that some diatoms can use siderophore-bound iron, and exhibit a species-specific recognition for siderophore types. In Phaeodactylum tricornutum, hydroxamate siderophores are taken up without previous reduction by a high-affinity mechanism that involves binding to the cell surface followed by endocytosis-mediated uptake and delivery to the chloroplast. The affinity recorded is the highest ever described for an iron transport system in any eukaryotic cell. Collectively, our observations suggest that there are likely a variety of iron uptake mechanisms in diatoms besides the well-established reductive mechanism. We show that iron starvation-induced protein 1 (ISIP1) plays an important role in the uptake of siderophores, and through bioinformatics analyses we deduce that this protein is largely diatom-specific. We quantify expression of ISIP1 in the global ocean by querying the Tara Oceans atlas of eukaryotic genes and show a link between the abundance and distribution of diatom-associated ISIP1 with ocean provinces defined by chronic iron starvation.
Keywords: Gene Knockdown Techniques; železo; endocytóza; Species Specificity; Aquatic Organisms; Chloroplasts; transport proteinů; chloroplasty; siderofory; Diatoms; Iron; vodní organismy; genový knockdown; druhová specificita; Endocytosis; rozsivky; Siderophores; Protein Transport